GC-MS analysis of bioactive constituents of Aristolochia bracteolata Linn with in-vitro antioxidant properties - Trayee Sarkar Das,Latha Ramesh,Paul Agastian (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study was to evaluate the antioxidant activity of hexane, ethyl acetate and methanol extracts of Aristolochia bracteolata Linn. Hexane, ethyl acetate and methanol extract were prepared using soxhlet extraction. DPPH and GC-MS were also performed. Methanol extract showed increased scavenging activity on 2,2-diphenyl-picrylhydrazyl (DPPH) (IC50 270.12 ±1.12 µg/ml), hydroxyl (IC50 450.04 ± 0.71 µg/ml), nitric oxide (IC50 640.06 ± 1.24 µg/ml) and hydrogen peroxide (IC50 300.51 ± 0.67 µg/ml) radicals, as well as high reducing power. Methanol extract also showed strong suppressive effect on lipid peroxidation (IC50 400.01±1.23) and metal chelating ability of methanol extract showed moderate effect (IC50 680.09 ± 0.33) when compared to the reference standard. In the present study the methanol extract of Aristolochia bracteolata has been subjected to GC-MS (Gas Chromatography-Mass Spectrometery) analysis. Sixty chemical constituents have been identified, The major peaks from GC-MS results revealed the presence of seven different phytochemical constituents like dodecane (7.50%), tetradecane (7.31%), tridecane (6.59%), undecane (6.29%), pentadecane (3.99%), hexadecane (2.69%) and decane (1.49%) whereas some other minor peaks corresponds to the presence of other phytoconstituents with medicinal properties. The results so obtained in the present study clearly indicate that methanol extract has a significant potential and can be used as an antioxidant agent. The presence of various phytochemical constituents may further pave a way for finding a novel drug.Read associated Erratum: GC-MS analysis of bioactive constituents of Aristolochia bracteolata: Erratum with this article.
Keywords: Antioxidant,Aristolochia bracteolata,GC-MS,Phytoconstituents.